Experimental Study Solar Dryer System for Nila Fish - MARDHIKA UTAMA (NIM 13103073), PUTRA
Drying of fish is generally conducted to reduce water content until below 10% wet basis, as a mean to lengthen the duration of storage time. Testing of fish drying is conducted by using solar dryer at Solar Energy laboratory ITB. Solar dryer system consists of solar collector, drying chamber and blower to deliver air. 3 kg of Nila fish are tested in the solar dryer and parallel to this experiment 300 grams of Nila fish are dried using direct sun light. Experiment is conducted in March until June 2008. The air speed inside the drying chamber is varied between 0,27 m/s to 0,3 m/s. The drying rate, collector efficiency and drying efficiency are calculated and analyzed. Testing result showed data of experiment that the solar dryer can reduce the moisture content below 10%. Drying efficiency varies between 0,5% to 8,16%. Collector efficiency varies between 38,3% to 79,14%. Drying time of fish are 2-5 days with interruption during the night. Average drying rate varies between 0,0076-0,0013 g/s with air speed 0,27-0,3 m/s. Average temperature of the drying air varies between 26-380C. Fish quality obtained from the solar dryer is better than that obtained by direct sun drying.